Comparative Biochemical Analysis of Non-Diabetic Individuals with and without Metabolic Syndrome: A Cross-Sectional Study - Trivedi, Amit P.; Patel, Megha N.; Panchal, Khushbu R.; Patel, Dharmik S. (South Eastern European Journal of Public Health, 2024)
Introduction: Non-communicable diseases (NCDs) increasingly threaten public health and economic well-being worldwide, leading to substantial shifts in healthcare demands. Metabolic syndrome (MetS)—characterized by central obesity, insulin resistance, dyslipidemia, and hypertension—is a significant risk factor for type 2 diabetes and cardiovascular diseases. Preventing and managing MetS effectively requires a comprehensive understanding of its underlying biochemical processes. Objective: This study aims to identify key biochemical markers in non-diabetic individuals with MetS that may increase their risk for type 2 diabetes and cardiovascular diseases. Materials and Methods: In this cross-sectional study, we investigated biochemical differences in non-diabetic individuals with MetS. Ethical approval was obtained, and 118 participants aged 30 to 60 years were recruited from an outpatient clinic, with 59 individuals in the MetS group and 59 as controls. Blood samples, taken after fasting overnight, were analyzed for serum insulin, lipid profiles, and fasting plasma glucose. Results: The control group had an average age of 50.77 years, compared to 53.25 years in the MetS group. MetS participants exhibited significantly elevated postprandial blood sugar (PP2BS) (166.47 ± 21.89 mg/dL vs. 113.59 ± 18.11 mg/dL, p < 0.001) and fasting blood sugar (FBS) (113.57 ± 8.68 mg/dL vs. 103.02 ± 13.85 mg/dL, p < 0.001). Higher levels of triglycerides (214.16 ± 68.96 mg/dL vs. 118.55 ± 54.78 mg/dL, p < 0.001) and total cholesterol (203.35 ± 41.65 mg/dL vs. 183.0 ± 41.10 mg/dL, p = 0.0086) were also observed, alongside lower HDL levels (38.16 ± 6.50 mg/dL vs. 46.66 ± 12.18 mg/dL, p < 0.001). No significant differences were found in LDL cholesterol and HbA1c levels. Conclusion: In non-diabetic individuals with metabolic syndrome, elevated glucose, triglycerides, total cholesterol, and reduced HDL indicate higher cardiometabolic risk. HbA1c and LDL showed no significant differences, but monitoring these markers could aid in early intervention.